Nitrate improves growth in salt-stressed citrus seedlings through effects on photosynthetic activity and chloride accumulation - Iglesias, Domingo J.; Levy, Y.; Gómez-Cadenas, Aurelio; Tadeo, Francisco R.; Primo-Millo, Eduardo; Talón, Manuel (2017)
We analyzed the effects of nitrate availability on growth of Navelina (Citrus sinensis (L.) Osbeck) scions grafted on three citrus rootstocks differing in salt tolerance: Carrizo citrange (Citrus sinensis (L.) Osbeck x Poncirus trifoliata (L.) Raf.), Citrus macrophylla Wester and Cleopatra mandarin (Citrus reshni Hort. ex Tanaka). Salt stress reduced total plant biomass by 27-38%, whereas potassium nitrate supplementation partially counteracted this effect by increasing dry matter and new leaf area. Salinized Carrizo citrange had the greatest response to nitrate supplementation, whereas the effects on salinized Cleopatra mandarin and C. macrophylla were less apparent. Nitrogen and chlorophyll contents and photosynthetic activity also increased in leaves of the nitrate-supplemented salinized plants. In salinized plants, nitrate supplementation reduced leaf abscission, stimulated photosynthetic activity and increased growth of new leaves. The nitrate treatment did not modify chloride concentration in leaves, but it reduced chloride concentrations in Carrizo and Macro-phylla roots. Therefore, in both rootstocks, chloride content was similar in mature leaves, higher in immature leaves and lower in roots of the nitrate-supplemented salinized plants compared with salinized plants unsupplemented with nitrate. We suggest that the nitrate-induced stimulation of growth reduced chloride concentration in roots through the reallocation of chloride to new leaves.